Chondro-osseous Respiratory Epithelial Adenomatoid Hamartoma (COREAH) : A rare entity of nasal mass (Bangladesh Journal of Medical Science, 2018)
Chondro-osseous respiratory epithelial adenomatoid hamartoma (COREAH) is an extremely rare benign lesion of the nose and paranasal sinuses. Clinically the lesion presents as a polypoid mass and histologically can be easily confused with more threatening tumors such as inverted papilloma and sinonasal carcinoma. A correct and accurate diagnosis is really important as all of these lesions are treated by different surgical approach. Here we report a case of COREAH in a middle-age lady who presented with unilateral nasal mass with chronic nasal obstruction.Bangladesh Journal of Medical Science Vol.17(3) 2018 p.489-492